A Review of Hybrid Converter Topologies - Hossein Afshari; Oleksandr Husev; Oleksandr Matiushkin; Dmitri Vinnikov (Energies, 2022)
There is a growing interest in solar energy systems with storage battery assistance. There is a corresponding growing interest in hybrid converters. This paper provides a comprehensive review of hybrid converter topologies. The concept of a hybrid inverter is introduced and then classified into isolated and non-isolated structures based on using a galvanic transformer. The classification and description of each type are presented based on the features and applications. Furthermore, the most popular commercial solutions are investigated in terms of their simplicity, flexibility, efficiency, and battery technology. The summarizing features are presented through tables, and future trends for researchers to follow to develop efficient hybrid converters are discussed. This review paper is intended as a convenient reference for hybrid converter users.